Reduction of delivery times in a Peruvian metal-mechanical company. (20th October 2020) - Landa, Jazmin V.; Suárez, Angie R.; Mendoza, Pablo F.; Alvarez, José C.
This study seeks to achieve the highest level of service and productivity in an industry in the metal-mechanical sector. For this, observations, a study of methods and times were carried out to investigate the limiting factors of the progression of productivity in an environment of manufacture of electrical panels. The captured data was used to identify the different wastes present in the production system, suggest, and validate sustainable manufacturing system strategies using a system simulation model. The proposed solution used for this research incorporates lean thinking and its tools such as the value flow map (VSM), the theory of constraints (TOCs), 5S, the Kanban production system, and the standardisation of working methods. The implementation of the proposed methodology resulted in the improvement of the general performance of the company under study with a 15.74% reduction in cycle time.